CAUCASIAN HOME: HISTORY AND REALITY - Oganesan, A Z; Magomedhanov, M M (History, Archeology and Ethnography of the Caucasus, 2015)
The article highlights the questions of the history and contemporary realities of inter-ethnic relations in the Caucasus in the context of using the experience of the Russian Empire in this area. The basic characteristics of the Caucasian identity are characterized. It is noted that in the nineteenth century the unity of the Caucasian peoples in a single state contributed to the development of their economic and spiritual life, strengthening the links between them, formation of an atmosphere of inter-ethnic harmony. Argues that the Caucasus has great potential for integration at regional and global levels, that the prospects of the Caucasian House are in ensuring the interests and conditions of development of each nation, and not in the aggravation of inter-state and inter-ethnic tensions.